Comparison of Hemodynamic Response to Endotracheal Intubation with Nebulized Lignocaine and Dexmedetomidine: a Prospective Randomized Controlled Trial - Dash, Sulochana; Sree, Pasupala Subba Kavya; Panigrahy, Sasmita; Sahu, Alisha; Nath, Abinash Kumar; Rani, Pedireddy Sobha (Journal of Anaesthesia and Pain, 2024)
Background: Though different studies have compared intravenous (IV) lignocaine with dexmedetomidine for blunting laryngoscopic and intubation response, there is hardly any study comparing nebulized Lignocaine and dexmedetomidine for the same. This study compared the effectiveness of nebulized dexmedetomidine and Lignocaine for blunting hemodynamic response to laryngoscopy and intubation.Methods: This prospective randomized double-blinded study among 60 patients was divided into two equal groups of 30 (groups D and L). Group D patients were nebulized with 1 µg/kg of dexmedetomidine diluted in 0.9% saline to a total volume of 4 ml, and Group L patients were nebulized with 4ml of 4% Lignocaine hydrochloride in the preoperative room over 5 min. After induction of general anesthesia, laryngoscopy and intubation were performed, and hemodynamic changes were recorded for statistical analysis. A two-sample t-test was applied to compare means in two groups with a confidence interval of 95%.Result The Dexmedetomidine group demonstrated a significant difference, with lower values of mean heart, systolic, diastolic, and mean arterial pressure rate immediately before laryngoscopy till 10 minutes postintubation (recorded at 2 mins intervals till 10mins) compared to the lignocaine group. The p-values for all the parameters were < 0.001, underlining the robustness of our findings.Conclusion: Nebulised Dexmedetomidine before laryngoscopy is not just an alternative technique, but a superior one for blunting the hemodynamic response to laryngoscopy and endotracheal intubation. It outperforms Nebulised Lignocaine without significant adverse effects, such as postoperative sore throat and sedation, making a compelling case for its adoption in clinical practice.